Towards the business process model as code approach - Orlovskyi, D. L.; Kopp, A. M. (My University, 2020)
Business process management and its modeling capabilities are vital for successful analysis, improvement and automation of core organizational processes. However, manual process model design is error-prone, while graphic models are almost not traceable and reusable. Thus, Everything as Code practice, successfully used in software engineering, can be also applied to business process modeling domain. This study shows the idea of process model as code approach and early results in this field.
Keywords: business process model; business process model as code practice; model quality; traceability; reusability